Are diel vertical migrations of European perch (Perca fluviatilis L.) early juveniles under direct control of light intensity? Evidence from a large field experiment. (15th February 2018) - Sajdlová, Zuzana; Frouzová, Jaroslava; Draštík, Vladislav; Jůza, Tomáš; Peterka, Jiří; Prchalová, Marie; Říha, Milan; Vašek, Mojmír; Kubečka, Jan; Čech, Martin
Abstract: Diel vertical migrations (DVMs) belong among the most pronounced movements in the aquatic environment. A general pattern of DVMs has been well described, particularly in European perch ( Perca fluviatilis ), but whether the migrations are directly controlled by light and what is the ultimate cause of the diel vertical shifts, remains poorly understood. Undertaking a large‐scale field experiment in a thermally stratified, canyon‐shaped reservoir, we demonstrated for the first time that DVMs of a bathypelagic early juveniles community, dominated by European perch larvae and juveniles prior the metamorphosis, were under direct control of the light intensity; that is, they did not operate as a genetically fixed behaviour. Prior to the experiment, the depth distribution of the bathypelagic perch early juveniles was strongly correlated with the light intensity on the water surface ( p  < .001). The community underwent regular DVMs between the epilimnion (depth <2.0 m) and hypolimnion (depth >3.0 m) reaching a maximum amplitude of 13 m. Hydroacoustic recordings by the echosounder SIMRAD EK 60 (120 and 400 kHz) showed that during the experiment, when the surface was covered with a large black non‐transparent foil (2500 m 2 ; simulated conditions of complete and constant darkness), the regular vertical movement of the bathypelagic perch early juveniles was interrupted and the community occupied the epilimnion constantly for 24 hr. Immediately after the foil was removed at midday, the bathypelagic perch early juveniles were exposed to a steep increase in light intensity (from <1 LUX to >100 × 10 3 LUX) and they escaped into the hypolimnion where they were safe from visual predation which took place in the bright surface layers (epilimnion particularly). Our findings imply that occupying a deep, dark refuge in the daytime is essential for the survival of perch in their early life stage.